2022
DOI: 10.3390/nu14173482
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Xenobiotics Derived from Food Processing: Association with Fecal Mutagenicity and Gut Mucosal Damage

Abstract: Whereas the mechanisms underlying the association of toxic dietary xenobiotics and cancer risk are not well established, it is plausible that dietary pattern may affect the colon environment by enhancing or reducing exposure to mutagens. This work aimed to investigate the association between xenobiotics intake and different stages of intestinal mucosal damage and colorectal cancer (CRC) screening and examine whether these associations may be mediated by altered intestinal mutagenicity. This was a case control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 65 publications
1
22
0
Order By: Relevance
“…These findings could help to support the possible relationship between alcohol intake and the increased risk of intestinal polyps development. 26 In the control subjects, volunteers with intake of total polyphenols ≥650 mg day −1 and or calcium intake <900 mg day −1 revealed an increased abundance of Veillonellaceae. A decreased abundance of the genus Veillonella , a member of the family Veillonellaceae, has been previously associated with gut mucosal damage in humans.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…These findings could help to support the possible relationship between alcohol intake and the increased risk of intestinal polyps development. 26 In the control subjects, volunteers with intake of total polyphenols ≥650 mg day −1 and or calcium intake <900 mg day −1 revealed an increased abundance of Veillonellaceae. A decreased abundance of the genus Veillonella , a member of the family Veillonellaceae, has been previously associated with gut mucosal damage in humans.…”
Section: Discussionmentioning
confidence: 98%
“…Human samples of faeces and anamnesis, and analytical data were also collected at the time of recruitment, as described elsewhere. 26 A total of 60 volunteers for which dietary information and faecal samples were available were included in the study. According to the screening colonoscopy results, volunteers were classified as controls not showing any alteration of the intestinal mucosa ( n = 25), or polyps ( n = 35) in the case of those volunteers showing the presence of one or more intestinal polyps in the colonic mucosa.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Volunteers rated each item on an intensity scale ranging from 0 to 3, with a maximum possible score of 63 points. The severity of depressive symptoms was categorized as minimal (0-13 points), mild (14)(15)(16)(17)(18)(19), moderate (20)(21)(22)(23)(24)(25)(26)(27)(28), or severe (29-63) using previously established references [59,60].…”
Section: Severity Of Depressive Symptomsmentioning
confidence: 99%
“…Recent literature has shown that processed foods have a negative impact on dietary quality and health due to the poor nutrient density, their high additive content, and association with higher intakes of sugars and trans-fatty acids [14]. Sugar-sweetened beverages and processed meats [14,15] have been associated with an increased risk of non-communicable diseases including colorectal cancer [16][17][18]. Along with that, the scarce consumption of fruits, vegetables and whole grains may lead to a reduced intake of fiber or (poly)phenols, which have been identified as key players in microbiota modulation in addition to their anti-inflammatory and antioxidant properties [17,19,20].…”
Section: Introductionmentioning
confidence: 99%